Designing a School-Based, Complex Public Health Intervention to Improve Iodine Awareness in Adolescents in Six Countries - Bodil Just Christensen; Natalia Cecon-Stabel; Synnøve Næss Sleire; Lisbeth Dahl; Signe Svarrer Skovgaard-Pedersen; Vivien Henck; Phil Pendt; Muhammad Nasir Khan Khattak; Elias Peschke; Henry Völzke; Mithila Faruque; Rehman Mehmood Khattak; et al. (Nutrients, 2026)
Background: Iodine is an essential micronutrient required for foetal development, cognitive function, and metabolic regulation; however, suboptimal iodine status remains a public health concern in Europe and other regions. Improving food literacy related to iodine may support healthier dietary choices during adolescence, a critical life stage for establishing long-term habits. This intervention development study describes the development of The ABC of Iodine Teaching Programme within the EUthyroid2 project, designed to enhance iodine-related knowledge and awareness among adolescents aged 13–17 years across six regions (UK, Republic of Cyprus, Slovenia, Germany, Bangladesh, and Pakistan). Methods: The intervention was developed according to the Behaviour Change Wheel, targeting capability, opportunity, and motivation, and informed by guidance for complex interventions. The programme was comprised of three flexible, culturally adapted modules integrating lectures on iodine physiology, deficiency risks, WHO recommendations, and locally relevant dietary sources. Active learning strategies, including collaborative tasks and personalised feedback through an Iodine Feedback Tool, were included. Materials were translated and adapted to local contexts and implemented in a hybrid format combining printed booklets with QR-linked digital resources. Results: The primary outcome of the intervention development process was The ABC of Iodine Teaching Programme, a multi-component, scalable educational intervention aligned with principles of food literacy, active learning and behaviour change theory. It incorporated behaviour change techniques and context-specific adaptations to facilitate engagement and knowledge acquisition in school settings. The programme is currently under evaluation in participating regions. Conclusions: This study presents the systematic development of a complex teaching programme. By combining behaviour change theory with innovative and context-sensitive educational strategies, The ABC of Iodine Teaching Programme provides a flexible and scalable framework for improving iodine-related food literacy among adolescents. Its effectiveness will be determined through the ongoing evaluation studies.